Post-polypectomy colonoscopy surveillance: European Society of Gastrointestinal Endoscopy (ESGE) Guideline – Update 2020 - Hassan, Cesare; Antonelli, Giulio; Dumonceau, Jean-Marc; Regula, Jaroslaw; Bretthauer, Michael; Chaussade, Stanislas; Dekker, Evelien; Ferlitsch, Monika; Gimeno-Garcia, Antonio; Jover, Rodrigo; Kalager, Mette; Pellisé, Maria; et al. (Endoscopy, 2020)
Main Recommendations The following recommendations for post-polypectomy colonoscopic surveillance apply to all patients who had one or more polyps that were completely removed during a high quality baseline colonoscopy. 1 ESGE recommends that patients with complete removal of 1 – 4 < 10 mm adenomas with low grade dysplasia, irrespective of villous components, or any serrated polyp < 10 mm without dysplasia, do not require endoscopic surveillance and should be returned to screening. Strong recommendation, moderate quality evidence. If organized screening is not available, repetition of colonoscopy 10 years after the index procedure is recommended. Strong recommendation, moderate quality evidence. 2 ESGE recommends surveillance colonoscopy after 3 years for patients with complete removal of at least 1 adenoma ≥ 10 mm or with high grade dysplasia, or ≥ 5 adenomas, or any serrated polyp ≥ 10 mm or with dysplasia. Strong recommendation, moderate quality evidence. 3 ESGE recommends a 3 – 6-month early repeat colonoscopy following piecemeal endoscopic resection of polyps ≥ 20 mm. Strong recommendation, moderate quality evidence. A first surveillance colonoscopy 12 months after the repeat colonoscopy is recommended to detect late recurrence. Strong recommendation, high quality evidence. 4 If no polyps requiring surveillance are detected at the first surveillance colonoscopy, ESGE suggests to perform a second surveillance colonoscopy after 5 years. Weak recommendation, low quality evidence. After that, if no polyps requiring surveillance are detected, patients can be returned to screening. 5 ESGE suggests that, if polyps requiring surveillance are detected at first or subsequent surveillance examinations, surveillance colonoscopy may be performed at 3 years. Weak recommendation, low quality evidence. A flowchart showing the recommended surveillance intervals is provided (Fig. 1).